Reading as Re-reading: The Poetic Function of the Grammatical Ambiguity in Jer 51:20-24 - Popko, Łukasz (The Biblical Annals, 2018)
The grammatical ambiguity of Jer 51:20-24 results in three possible interpretations: 1) Babylon as God’s weapon; 2) an announcement of Babylon’s demise; 3) God as the victorious ruler of the world history. The ambiguity should be considered as a poetic trope.